THE LHCspin PROJECT: A POLARISED GAS TARGET AT THE LHC - Santimaria, Marco; Carassiti, Vittore; Ciullo, Giuseppe; Di Nezza, Pasquale; Lenisa, Paolo; Mariani, Saverio; Pappalardo, Luciano Libero; Steffens, Erhard (Acta Physica Polonica B, Proceedings Supplement, 2025)
LHCb is the only experiment at the LHC able to reconstruct simultaneously events from beam–beam and beam–gas collisions taking place in a gas storage cell. The aim of the LHCspin project is to bring spin physics at the LHC for the first time by injecting polarised hydrogen and deuterium. This would enable the high-energy LHC beam and the peculiar forward geometry of LHCb to explore the 3D structure of matter in a unique kinematic regime and by means of probes that are not accessible in other facilities.
CRIS-Team Scopus Importer:2025-04-01